PERAN LEMBAGA KONSULTASI KESEJAHTERAAN KELUARGA KOTA CIMAHI DALAM PEMBERDAYAAN PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Nuradhawati, Rira; Permana, Danny; Rahmandika, Muhammad Aldi (Caraka Prabu : Jurnal Ilmu Pemerintahan, 2022)
This study discusses how the role of LK3 Cimahi City in empowering women victims of domestic violence. The background of this research is based on the phenomenon of violence that happens to women which is usually carried out by those who are considered stronger. The forms of violence are physical and psychological. Many victims do not dare to speak up because they consider it a domestic problem and a disgrace to the family so that the role of institutions or organizations that can empower women victims of domestic violence is needed. The study of this research is to see how LK3 in carrying out its role to empower women victims of domestic violence. This study uses a qualitative method that produces descriptive data obtained through literature study, observation and in-depth interviews with informants. The informants in this study included LK3 employees, the community and also women victims of domestic violence who were considered capable of providing valid information.